Stability and loading properties of Curcumin encapsulated in saffron pollen - Yaser Jafari; Hossein Sabahi; Ali Hossein Rezayan (Food Chemistry Advances)
Curcumin (Cur), a polyphenolic compound with diverse pharmacological properties, was effectively encapsulated within saffron pollen (SP). The encapsulation process was validated using multiple analytical techniques, including fluorescence microscopy, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and Fourier transform infrared spectroscopy (FT-IR). Scanning electron microscopy (SEM) images revealed that Cur was integrated within the surface pores and the internal structure of SP. The adsorption isotherm of Cur onto SP was best described by the Freundlich isotherm model. The maximum loading capacity achieved was 14 % (w/w). TGA analysis indicated that the thermal stability of the SP/Cur complex was enhanced by 2.3 % and 20 % compared to their unencapsulated forms at temperature ranges of 0–300 °C and 300–600 °C, respectively. The DPPH assay demonstrated that the photostability of Cur in its encapsulated form was 4 times greater than that of free Cur after both were subjected to light exposure for 60 days. In conclusion, the findings substantiate that SP represents a novel and stable carrier for Cur.